Nonprofit organizations: theory, management, policy - Anheier, Helmut K. (Routledge, 2014)
In this new edition of his popular textbook, Nonprofit Organizations: Theory, Management, Policy, Helmut K. Anheier has fully updated, revised and expanded his comprehensive introduction to this field. The text takes on an international and comparative dimensions perspective, detailing the background and concepts behind these organizations and examining relevant theories and central issues.Anheier covers the full range of nonprofit organizations--service providers, membership organizations, foundations, community groups--in different fields, such as arts and culture, social services and education. He introduces central terms such as philanthropy, charity, community, social entrepreneurship, social investment, public good and civil society. Acknowledging and explaining how the field spills over from public management, through nonprofit management and public administration. This textbook is systematic in its treatment of theories, management approaches and policy analyses.The previous edition was winner of the Best Book Award at the American Academy of Management in 2006, and this new edition will fit both the North American and European schedules of academic teaching. Nonprofit Organizations: Theory, Management, Policy is an ideal resource for students on both undergraduate and post-graduate courses.